Before the bittersweet - Gammelin, Cherry Ann (Department of English Language and Literature, 2015)
Before the Bittersweet is an American story about the experiences of five teenagers during one summer in a small town on a lake in New England. The plot offers a realistic representation of what can happen in a Middle American society where ambition is often lacking, boredom is plentiful and the loss of innocence happens all too quickly. This story, foreshadowed by the natural beauty and darkness of its setting, runs about 46 000 words and brings a tone that is somewhat similar to J.D. Salinger’s The Catcher in the Rye.